Association of Labor With Neonatal Respiratory Outcomes at 36–40 Weeks of Gestation. Issue 3 (September 2019) - Plunkett, Beth A.; Sandoval, Grecio; Bailit, Jennifer L.; Reddy, Uma M.; Wapner, Ronald J.; Varner, Michael W.; Thorp, John M.; Caritis, Steve N.; Prasad, Mona; Tita, Alan T. N.; Saade, George R.; Sorokin, Yoram; et al.
Abstract : OBJECTIVE: To evaluate whether labor is associated with lower odds of respiratory morbidity among neonates born from 36 to 40 weeks of gestation and to assess whether this association varies by gestational age and maternal diabetic status. METHODS: We conducted a secondary analysis of women in the Assessment of Perinatal Excellence obstetric cohort who delivered across 25 U.S. hospitals over a 3-year period. Women with a singleton liveborn nonanomalous neonate who delivered from 36 to 40 weeks of gestation were included in our analysis. Those who received antenatal corticosteroids, underwent amniocentesis for fetal lung maturity, or did not meet dating criteria were excluded. Our primary outcome was composite neonatal respiratory morbidity, which included respiratory distress syndrome, ventilator support, continuous positive airway pressure, or neonatal death. Maternal characteristics and neonatal outcomes between women who labored and those who did not were compared. Multivariable logistic regression models were used to evaluate the association between labor and the primary outcome. Interactions between labor and diabetes mellitus and labor and gestational age were tested. RESULTS: Our analysis included 63, 187 women who underwent labor and 10, 629 who did not. There was no interaction between labor and diabetes mellitus ( P =.90). However, there was a significant interaction between labor and gestational age ( P =.01). In the adjusted model, labor was associated with lower odds of neonatal respiratory morbidity compared with no labor for neonates delivered from 36–39 weeks of gestation. A 1-week increase in gestational age was associated with a 1.2 times increase in the adjusted odds ratio for the neonatal outcome comparing labor and no labor. CONCLUSION: Labor was associated with lower odds of the composite outcome among neonates delivered from 36–39 weeks of gestation. The magnitude of this association varied by gestational age. The association was similar for women with or without diabetes mellitus. Abstract : Labor was associated with lower odds of respiratory morbidity among neonates delivered from 36 weeks to 39 weeks of gestation.